Pharmacist Involvement to Prevent and Manage HIV/AIDS in Indonesia: A Systematic Review - Firmansah, Moh.; Setiawan, Eko; Presley, Bobby; Christanti, Jene Vida; Irawati, Sylvi (Keluwih: Jurnal Kesehatan dan Kedokteran, 2023)
Abstract—Pharmacists’ involvement in the human immunodeficiency virus/acquired-immunodeficiency syndrome (HIV/AIDS) prevention and management program has been globally advocated. However, there is currently a lack of information on whether pharmacists’ roles in the program have been clearly articulated in the national policy records in countries with high scores on power distance and collectivism, such as Indonesia. This study aimed to explore the roles of pharmacists in the prevention and management of HIV/AIDS in Indonesia using a systematic review method. We systematically searched for relevant studies in three large medical databases (CINAHL, EMBASE, and PubMed) and for gray literature in both the Indonesian Pharmacist Association and the Ministry of Health websites, and the national regulation database. Only two studies gave a glimpse of pharmacists’ role in the prevention and management of patients with HIV/AIDS in Indonesia. However, activities conducted by pharmacists in each of these roles were not explicitly described. We found no official national policies mentioned the role of pharmacists in HIV/AIDS prevention and management. Since the practice of pharmacists is closely related to medications, including antiretroviral drugs, more research is needed to explore the role of pharmacists in the prevention and management of HIV/AIDS in a real-world context in Indonesia. Keywords: AIDS, HIV, pharmacist, indonesia Abstrak—Keterlibatan apoteker dalam program pencegahan dan tata laksana human immunodeficiency virus/acquired-immunodeficiency syndrome (HIV/AIDS) di dunia telah direkomendasikan. Akan tetapi, saat ini terdapat keterbatasan informasi mengenai apakah keberadaan peran apoteker dalam program tersebut telah dinyatakan dnegan jelas dalam dokumen kebijakan nasional di negara-negara yang memiliki skor tinggi pada power distance dan kolektivitas, seperti Indonesia. Penelitian ini bertujuan untuk menggali peran apoteker dalam pencegahan dan tata laksana HIV/AIDS di Indonesia menggunakan metode kajian sistematis. Secara sistematis, peneliti melakukan pencarian artikel penelitian terkait di tiga basis data medis yang besar (CINAHL, EMBASE, dan PubMed) dan pencarian gray literature di laman Ikatan Apoteker Indonesia dan Kementerian Kesehatan Republik Indonesia, serta di basis data peraturan nasional. Hanya dua penelitian yang memberikan secercah informasi mengenai peran apoteker dalam pencegahan dan tata laksana pasien dengan HIV/AIDS di Indonesia. Namun demikian, aktivitas spesifik yang dilakukan oleh apoteker tidak secara eksplisit digambarkan lebih lanjut. Peneliti tidak menemukan dokumen kebijakan nasional yang menyebutkan peran apoteker dalam pencegahan dan tata laksana HIV/AIDS. Oleh karena praktik kefarmasian berhubungan erat dengan obat, termasuk obat-obat antiretrovirus, maka dibutuhkan lebih banyak penelitian untuk menggali peran apoteker dalam pencegahan dan tata laksana HIV/AIDS pada konteks dunia-nyata di Indonesia. Kata kunci: AIDS, HIV, apoteker,indonesia